Elucidating heterogeneity of IgA1 hinge-region O-glycosylation by use of MALDI-TOF/TOF mass spectrometry: role of cysteine alkylation during sample processing - Franc, Vojtěch; Řehulka, Pavel; Raus, Martin; Stulík, Jiří; Novak, Jan; Renfrow, Matthew B; Šebela, Marek (Journal of proteomics, 2013)
UNLABELLED: Determining disease-associated changes in protein glycosylation provides a better understanding of pathogenesis. This work focuses on human immunoglobulin A1 (IgA1), where aberrant O-glycosylation plays a key role in the pathogenesis of IgA nephropathy (IgAN). Normal IgA1 hinge region carries 3 to 6 O-glycans consisting of N-acetylgalactosamine (GalNAc) and galactose (Gal); both sugars may be sialylated. In IgAN patients, some O-glycans on a fraction of IgA1 molecules are Gal-deficient. Here we describe a sample preparation protocol with optimized cysteine alkylation of a Gal-deficient polymeric IgA1 myeloma protein prior to in-gel digestion and analysis of the digest by MALDI-TOF/TOF mass spectrometry (MS). Following a novel strategy, IgA1 hinge-region O-glycopeptides were fractionated by reversed-phase liquid chromatography using a microgradient device and identified by MALDI-TOF/TOF tandem MS (MS/MS). The acquired MS/MS spectra were interpreted manually and by means of our own software. This allowed assigning up to six O-glycosylation sites and demonstration, for the first time, of the distribution of isomeric O-glycoforms having the same molecular mass, but a different glycosylation pattern. The most abundant Gal-deficient O-glycoforms were GalNAc4Gal3 and GalNAc5Gal4 with one Gal-deficient site and GalNAc5Gal3 and GalNAc4Gal2 with two Gal-deficient sites. The most frequent Gal-deficient sites were at Ser230 and/or Thr236. BIOLOGICAL SIGNIFICANCE: In this work, we studied the O-glycosylation in the hinge region of human immunoglobulin A1 (IgA1). Aberrant glycosylation of the protein plays a key role in the pathogenesis of IgA nephropathy. Thus identification of the O-glycan composition of IgA1 is important for a deeper understanding of the disease mechanism, biomarker discovery and validation, and implementation and monitoring of disease-specific therapies. We developed a new procedure for elucidating the heterogeneity of IgA1 O-glycosylation. After running a polyacrylamide gel electrophoresis under denaturing conditions, the heavy chain of IgA1 was subjected to in-gel digestion by trypsin. O-glycopeptides were separated from the digest on capillary columns using a microgradient chromatographic device (replacing commonly used liquid chromatographs) and subjected to MALDI-TOF/TOF mass spectrometry (MS) and tandem mass spectrometry (MS/MS) involving post-source decay fragmentation. We show that the complete modification of cysteines by iodoacetamide prior to electrophoresis is critical for successful MS/MS analyses on the way to deciphering the microheterogeneity of O-glycosylation in IgA1. Similarly, the removal of the excess of the reagent is equally important. The acquired MS/MS allowed assigning up to six O-glycosylation sites and identification of isomeric O-glycoforms. We show that our simplified approach is efficient and has a high potential to provide a method for the rapid assessment of IgA1 heterogeneity that is a less expensive and yet corroborating alternative to LC-(high-resolution)-MS protocols. The novelty and biological significance reside in the demonstration, for the first time, of the distribution of the most abundant isoforms of HR O-glycopeptides of IgA1. As another new feature, we introduce a software solution for the interpretation of MS/MS data of O-glycopeptide isoforms, which provides the possibility of fast and easier data processing. This article is part of a Special Issue entitled: Posttranslational Protein modifications in biology and Medicine.
Keywords: ECD; CHCA; tandem mass spectrometry; CAM; Human immunoglobulin A1 (IgA1); PSD; hinge region; DTT; MS; α-cyano-4-hydroxycinnamic acid; Fourier transform ion cyclotron resonance; liquid chromatography; FT-ICR; IAM; electron transfer dissociation; HR; Microgradient separation; O-glycosylation; cystein; electron capture dissociation; immunoglobulin A; mass spectrometry; odběr biologického vzorku; FEP; alkylace; iodoacetamide; IgA nefropatie; post-source decay; PAM; TFA; IgA; matrix-assisted laser desorption/ionization time-of-flight; dithiothreitol; LC; Glycopeptide; MS/MS; trifluoroacetic acid; lidé; propionamidation; Humans; reversed-phase liquid chromatography; MALDI-TOF; Specimen Handling; Alkylation; Mass spectrometry; imunoglobulin A; ETD; spektrometrie hmotnostní - ionizace laserem za účasti matrice; RPLC; IgAN; fluorinated ethylene propylene; ACN; glykosylace; acetonitrile; Immunoglobulin A; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; IgA nephropathy; carbamidomethylation; Glycosylation; Cysteine; Glomerulonephritis, IGA